2011
DOI: 10.1007/s13213-010-0188-z
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic ice cream: viability of probiotic bacteria and sensory properties

Abstract: Ice cream is a dairy product with good potential to act as a food carrier for probiotic bacteria. The incorporation of probiotic bacteria into ice cream is highly advantageous since, in addition to making a functional healthy food, ice cream in itself contains beneficial substances such as dairy raw materials, vitamins and minerals, and is consumed by the general population. Also, compared with fermented milks as a vehicle, ice cream supports considerably greater viability of probiotic strains during productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
116
1
19

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 63 publications
(101 reference statements)
4
116
1
19
Order By: Relevance
“…This attribute is known as "viability," namely adequate number of live probiotic cells in a food product at time of consumption (Mortazavian et al 2010). No general agreement has been established on the recommended and suggested levels ranging from 10 6 to over 10 7 cfu.mL −1 (Ferdousi et al 2013;Korbekandi et al 2011;Mohammadi et al 2011a;Mortazavian et al 2010Mortazavian et al , 2011. However, it is generally recommended that probiotic culture must be present in the product at minimum numbers of 10 7 cfu.mL −1 (IDF 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This attribute is known as "viability," namely adequate number of live probiotic cells in a food product at time of consumption (Mortazavian et al 2010). No general agreement has been established on the recommended and suggested levels ranging from 10 6 to over 10 7 cfu.mL −1 (Ferdousi et al 2013;Korbekandi et al 2011;Mohammadi et al 2011a;Mortazavian et al 2010Mortazavian et al , 2011. However, it is generally recommended that probiotic culture must be present in the product at minimum numbers of 10 7 cfu.mL −1 (IDF 1992).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, diversity of probiotic foods has increased on the market. Nowadays, probiotics can be found in non-fermented dairy products such as milk (Shin et al 2000), ice cream (Mohammadi et al 2011a) and dairy dessert , and non-dairy products such as fruit juices, cereal-based foods (Helland et al 2004), and meat-based products .…”
Section: Introductionmentioning
confidence: 99%
“…Sugars can reduce probiotic viability by osmotic stress and also increase their survivability by cryoprotective and prebiotics properties of sugars. These sugars effects on probiotics depend on the type and concentration of sugars, type of probiotic organism, freezing temperature and rate, freezing technology and storage time (Mohammadi et al, 2011). Refined sugar (e.g., lactose…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation helps to protect the bacterial cells from the hostile environment of the food product, as well as the gastrointestinal tract, thus potentially preventing cell loss (Homayouni et al 2008). It may cause an appropriate cell release in the intestinal medium (Mohammadi et al 2011). Shah and Ravula (2000) reported that the survival of probiotic bacteria in fermented frozen desserts improved with encapsulation.…”
Section: Introductionmentioning
confidence: 99%